New Approaches and Treatment Combinations for the Management of Chronic Myeloid Leukemia - Westerweel, Peter E.; te Boekhorst, Peter A. W.; Levin, Mark-David; Cornelissen, Jan J. (Frontiers in Oncology, 2019)
Current treatment of chronic myeloid leukemia (CML) with tyrosine kinase inhibitors (TKI) is effective in many patients, but is not curative and frequently limited by intolerance or resistance. Also, treatment free remission is a novel option for CML patients and requires reaching a deep molecular remission, which is not consistently achieved with TKI monotherapy. Together, multiple unmet clinical needs remain and therefore the continued need to explore novel treatment strategies. With increasing understanding of CML biology, many options have been explored and are under investigation. This includes the use asciminib as first in class inhibitor targeting the myristoyl pocket of BCR-ABL, combination treatments with established non-TKI drugs such as interferon and drugs with novel targets relevant to CML biology such as gliptins and PPARγ agonists. Together, an overview is provided of treatment strategies in development for CML beyond current TKI monotherapy.